2005
DOI: 10.1074/jbc.m506069200
|View full text |Cite
|
Sign up to set email alerts
|

The Disintegrin ADAM9 Indirectly Contributes to the Physiological Processing of Cellular Prion by Modulating ADAM10 Activity

Abstract: The cellular prion protein (PrP c ) is physiologically cleaved in the middle of its 106 -126 amino acid neurotoxic region at the 110/ 1112112 peptidyl bond, yielding an N-terminal fragment referred to as N1. We recently demonstrated that two disintegrins, namely ADAM10 and ADAM17 (TACE, tumor necrosis factor alpha converting enzyme) participated in both constitutive and protein kinase C-regulated generation of N1, respectively. These proteolytic events were strikingly reminiscent of those involved in the socal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
79
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(88 citation statements)
references
References 38 publications
6
79
1
1
Order By: Relevance
“…However, a protein similar to F35 is generated in the healthy human brain when PrP c is endoproteolized into 110/111 residues through ADAMs in a Protein kinase C (PKC)-dependent way, thereby generating a C-terminal fragment termed C1 (Cisse et al, 2005;Chen et al, 1995;Harris et al, 1993;Vincent et al, 2000;Vincent et al, 2001). A shorter fragment, within the OR region (residues 90/91), the C2, is generated in pathological conditions and poor data have yet been provided about this cleavage (Chen et al, 1995).…”
Section: Bcl-2/bax and Prp C -Truncated Mouse Modelsmentioning
confidence: 99%
“…However, a protein similar to F35 is generated in the healthy human brain when PrP c is endoproteolized into 110/111 residues through ADAMs in a Protein kinase C (PKC)-dependent way, thereby generating a C-terminal fragment termed C1 (Cisse et al, 2005;Chen et al, 1995;Harris et al, 1993;Vincent et al, 2000;Vincent et al, 2001). A shorter fragment, within the OR region (residues 90/91), the C2, is generated in pathological conditions and poor data have yet been provided about this cleavage (Chen et al, 1995).…”
Section: Bcl-2/bax and Prp C -Truncated Mouse Modelsmentioning
confidence: 99%
“…We also showed that ADAM9 indirectly participated in N1 formation, by modulating ADAM10 activity (Alfa Cissé et al, 2005). The mechanisms by which ADAM17 is modulated by PKC and upregulates N1 formation remained to be established.…”
Section: Introductionmentioning
confidence: 99%
“…This was achieved by stimulating serotonergic and noradrenergic neurons with antibodymediated PrP C cross-linking that, by triggering Fyn-dependent NADPH oxidase two distinct endo-proteolytic events, termed α-and β-cleavage, of which the α-cleavage implicates ADAM9, ADAM10 and ADAM17 (TACE). [33][34][35] Although the latter report has recently been questioned, 32 the patho-physiologic relevance of PrP C shedding and of the endo-proteolytic processes remains unclear.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%